2012
DOI: 10.1590/s0101-60832012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Marcadores periféricos e a fisiopatologia do transtorno bipolar

Abstract: Introdução: O entendimento da fisiopatologia do transtorno bipolar vem tendo avanços consistentes nos últimos anos. Um enfoque na relação entre carga alostática e alterações sistêmicas vem tomando corpo, com o objetivo de se entender a frequente progressão da doença. Proeminentes entre os mediadores periféricos têm sido as moléculas que poderiam ser amplamente agrupadas em neurotrofinas, marcadores de estresse oxidativo e marcadores inflamatórios. Objetivo: Descrever achados recentes em relação à fisiopatologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 98 publications
0
3
0
2
Order By: Relevance
“…Regarding oxidative stress, brain cells are more vulnerable to its damage as they present fewer antioxidant enzymes and a high level of oxidant metabolism ( Olmez and Ozyurt, 2012 ). Research has showed an imbalance between oxidative damage and antioxidant defenses in BD ( Magalhães et al, 2012 ; Pfaffenseller et al, 2013 ); depressive and manic episodes are associated with elevated oxidative stress activity ( Andreazza et al, 2007 ; Machado-Vieira et al, 2007 ). In a review, Bauer et al (2014) found results suggesting that elevated levels of peripheral inflammatory cytokines and oxidative stress and reduced levels of neurotrophic factors were associated with poorer cognitive performance in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding oxidative stress, brain cells are more vulnerable to its damage as they present fewer antioxidant enzymes and a high level of oxidant metabolism ( Olmez and Ozyurt, 2012 ). Research has showed an imbalance between oxidative damage and antioxidant defenses in BD ( Magalhães et al, 2012 ; Pfaffenseller et al, 2013 ); depressive and manic episodes are associated with elevated oxidative stress activity ( Andreazza et al, 2007 ; Machado-Vieira et al, 2007 ). In a review, Bauer et al (2014) found results suggesting that elevated levels of peripheral inflammatory cytokines and oxidative stress and reduced levels of neurotrophic factors were associated with poorer cognitive performance in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…Isso leva a supressão da resposta de estresse fisiológico baseado no feedback negativo (alostase), ou a uma alteração na quantidade de receptores nessas áreas neurais e, consequentemente, os níveis baixos de cortisol podem causar uma importante mudança no medo e na resposta de luta/fuga fisiológica (Carvalho et al, 2016). Esse mesmo processo está envolvido na gênese de alguns distúrbios psiquiátricos como o transtorno bipolar, especialmente se a criança tiver uma predisposição genética (Magalhães, Fries & Kapczinski, 2012).…”
Section: Resultsunclassified
“…Furthermore, IL-1β levels were also significantly elevated in chronic euthymic BD (Hamdani et al, 2013;Goldsmith et al, 2016). This IL-1 activates the transcription factor NF-κB, which in turn enhances the expression and release of IL-6, IL-8, and interferon-gamma (Magalhães et al, 2012;Kany et al, 2019) Thus, Rowland et al (2018) concluded that while no single biomarker was able to differentiate mood phases or evaluate the stages of the disease, specific combinations including IL-6, BDNF, TNF-α, TNFR1, IL-2, IL-10, and IL-4, were correlated with the disease's stages. These findings demonstrate a significant link between the immune system and BD pathophysiological pathways.…”
Section: Inflammatory Cytokinesmentioning
confidence: 95%